2019
DOI: 10.1093/jas/skz122.141
|View full text |Cite
|
Sign up to set email alerts
|

144 Effect of sodium butyrate (SB) on growth performance and complete blood cell count in nursery pigs: Two facility study

Abstract: A total of 344 weaned pigs (21 ± 2 d of age) were used at University of Arkansas (UA, n = 2 16) and University of Illinois at Urbana-Champaign (UIUC, n = 128) to evaluate increasing level of sodium butyrate (SB) on growth performance and complete blood cell count. Pigs at each facility were blocked by initial BW and randomly allotted to 1 of 4 dietary treatments with 9 replications/diet and 6 pigs/pen at UA; and 8 replications/diet and 4 pigs/pen at UIUC. Treatments included a control corn-soybean-meal based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… Zhao et al (2018) reported that dietary fiber increases the butyrate-producing bacteria and improves growth performance of weaned piglets. Tsai et al (2019) discovered that feeding sodium butyrate during the nursery phase tended to alter blood cell count and improve growth performance of weaned pigs. In the present study, the VFAs of ileum and cecum were increased in the FCSM group than that in the SBM group.…”
Section: Discussionmentioning
confidence: 99%
“… Zhao et al (2018) reported that dietary fiber increases the butyrate-producing bacteria and improves growth performance of weaned piglets. Tsai et al (2019) discovered that feeding sodium butyrate during the nursery phase tended to alter blood cell count and improve growth performance of weaned pigs. In the present study, the VFAs of ileum and cecum were increased in the FCSM group than that in the SBM group.…”
Section: Discussionmentioning
confidence: 99%